HALLYU SEBAGAI KASUS KOMUNIKASI PEMASARAN DAN KOMUNIKASI KORPORASI INTERNASIONAL - Nugroho, Aloisius Agus (School of Communication - Atma Jaya Catholic University of Indonesia, 2022)
In international-marketing communication, there is a relatively new phenomenon, the name of which is hallyu, meaning Korean wave. The term hallyu refers to the global popularity of Korean pop culture, beginning with China, being followed by Japan, at the turn of the millennium. In fact, hallyu can be divided into three stages. The purpose of this research is to understand hallyu from the context of history. In the first stage, mostly younger generation from many parts of the world simply fall in love with the so-called K-drama and K-pop music. In the second stage, those who have been bewitched by K-drama and K-pop do travelling to South Korea, especially to shooting places of K-drama such as Nami Island. In the third stage, they will become consumers of almost everything that can remind them of K-drama or K-pop. At least, some of them have been bewitched by Korean corporate communication that is supported by the Korean government.